1999
DOI: 10.1093/hmg/8.12.2325
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Gene Encoding KRIT1, a Krev-1/rap1a Binding Protein, Cause Cerebral Cavernous Malformations (CCM1)

Abstract: Cerebral cavernous malformations (CCM) are congenital vascular anomalies of the brain that can cause significant neurological disabilities, including intractable seizures and hemorrhagic stroke. One locus for autosomal dominant CCM ( CCM1 ) maps to chromosome 7q21-q22. Recombination events in linked family members define a critical region of approximately 2 Mb and a shared disease haplotype associated with a presumed founder effect in families of Mexican-American descent points to a potentially smaller region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
224
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(231 citation statements)
references
References 49 publications
(66 reference statements)
5
224
0
2
Order By: Relevance
“…Coding exons of the Krit1 and MGC4607 genes were amplified using primers described previously (Sahoo, et al, 1999;Liquori, et al, 2003). Coding exons of the PDCD10 gene were amplified using the following primers:…”
Section: Mutation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Coding exons of the Krit1 and MGC4607 genes were amplified using primers described previously (Sahoo, et al, 1999;Liquori, et al, 2003). Coding exons of the PDCD10 gene were amplified using the following primers:…”
Section: Mutation Analysismentioning
confidence: 99%
“…Based on the linkage of 20 families, Craig et al (Craig, et al, 1998) reported that CCM1 would account for 40% of all familial CCM cases, CCM2 would account for 20%, and CCM3 would account for 40%. The disease gene responsible for CCM1 encodes KRIT1 (KREV Interaction Trapped 1) (Laberge, et al, 1999;Sahoo, et al, 1999), and the disease gene for CCM2 encodes malcavernin (Liquori, et al, 2003;Denier, et al, 2004). Recently, mutations were identified in the PDCD10 (programmed cell death 10) gene in families not exhibiting KRIT1 or malcavernin mutations (Bergametti, et al, 2005), thus identifying a third causative gene.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, CCM1 was identified as the KRIT1 gene. 8,9 KRIT1, a protein of unknown function so far, was previously identified through a yeast two-hybrid screen designed to identify proteins interacting with Rap1A, a small Ras like GTPase protein. 10 KRIT1 encodes a 736 amino-acids protein containing four ankyrin domains, a FERM domain and a C-terminal portion interacting with Rap1A.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Later on, two other genes were found to be associated with CCM, CCM2/ OSM (osmosensing protein 1)/Malcavernin 35,36 and CCM3/ PDCD10 (programmed cell death 10). 37,38 Over 150 different germline mutations are identified in either one of these genes, predominantly resulting in loss of function.…”
Section: 32mentioning
confidence: 99%
“…Of the three CCM proteins, KRIT1/CCM1, is the first protein identified related to CCM 33,34 and is most extensively studied compared with CCM2 and CCM3. Therefore, we will predominantly focus on the molecular details described for CCM1.…”
Section: Molecular Details Of Ccm1mentioning
confidence: 99%